Segmentation and kinematics of the North America‐Caribbean plate boundary offshore Hispaniola. (10th November 2015) - Leroy, Sylvie; Ellouz‐Zimmermann, Nadine; Corbeau, Jordane; Rolandone, Frédérique; de Lépinay, Bernard Mercier; Meyer, Bertrand; Momplaisir, Roberte; Granja Bruña, José‐Luis; Battani, Anne; Baurion, Céline; Burov, Evgueni; Clouard, Valérie; et al.
Abstract: We explored the submarine portions of the Enriquillo–Plantain Garden Fault zone (EPGFZ) and the Septentrional–Oriente Fault zone (SOFZ) along the Northern Caribbean plate boundary using high‐resolution multibeam echo‐sounding and shallow seismic reflection. The bathymetric data shed light on poorly documented or previously unknown submarine fault zones running over 200 km between Haiti and Jamaica (EPGFZ) and 300 km between the Dominican Republic and Cuba (SOFZ). The primary plate‐boundary structures are a series of strike‐slip fault segments associated with pressure ridges, restraining bends, step overs and dogleg offsets indicating very active tectonics. Several distinct segments 50–100 km long cut across pre‐existing structures inherited from former tectonic regimes or bypass recent morphologies formed under the current strike‐slip regime. Along the most recent trace of the SOFZ, we measured a strike‐slip offset of 16.5 km, which indicates steady activity for the past ~1.8 Ma if its current GPS‐derived motion of 9.8 ± 2 mm a −1 has remained stable during the entire Quaternary.